The Reciprocal Relationship Between Health and Sports in Physical Fitness - Hasanuddin, M. Imran (Universitas Majalengka, 2025)
This literature review aims to understand the reciprocal relationship between health and sports in physical fitness. Fitness Fitness is a very important indicator of health for a person. Fitness is related to a person's physical ability and capability to carry out daily activities efficiently and effectively in a relatively long time without causing significant fatigue, in addition to still having energy reserves to carry out other activities. In the physical aspect, the scope of sports health plays a very clear role, because this aspect is the beginning of all forms of training. From the physical aspect, a coach or teacher can analyze and find out from the growth and development of an athlete, analyze the anatomy of the body so that the coach or teacher can guess the development of the athlete in its branches. In the spiritual aspect, it is very closely related to the self-confidence factor. This is also related to sports psychology, sports pedagogy, and sports sociology. While the environmental aspect greatly influences the development of athletes. The scope of sports health is closely related to the environmental aspect. This aspect can appear in athletes when they are stimulated by their environment.